High society - Patrick, John; Siegel, Sol C.; Walters, Charles (MGM/UA Home Video, 1956)
A sophisticated comedy with music. The preparation for the wedding of a headstrong society divorcee to a priggish self-made man is interrupted on the eve of the ceremony by the bride's easy going ex-husband and a debonair reported from a gossip magazine.